A study on choice of vacation area - Haznedar, Ali. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Scieences, 1986., 1986)
In tnis thesis vacation area and lodging choice, area activity of vacationers will be studied by analyzing various choice criteria. Area activity preference of vacationers are examined and preference types are identified, Vacationers are asked to give importance weights to vacation destination andaccomodation specific attri5utes. Association between sociodemograpnic and travel behavioral groups is analyzed through spearman-rank order coefficient and differentiation of ttlese groups is examined by employing discriminant analyses. Also those attri5utes differenting between these groups are identified. An assodation is only found between married and single visitors in ranking vacation area choice criteria while otner groups nave unique characteristics with respect to promotion activities, word of mouttl communication, previous experience, price and percieved risk which differentiate them from other groups. No differences are found between sociodemographic and travel behaviour groups in area activity preference except age groups where younger group and singles are more entertainmet-prone and active than those over 35 and married. Only married and singles were discriminated by lodging choice criteria wher.e.married gave more importance to health and appearance related attributes than singles. Hospitality, physical establishment and courtesy were identified as the most important factors influencing lodging choice of all groups. The research is performed through a field study and included a literature review and implications for area and hotel managers, newcomers to the industry, vacationers and travel researchers. Data were collected by a questionnaire administered to families couples and singles by convenience and interpreted through computer.
Keywords: Voyages and travels.; Vacations.; Travel.